Britain and the new Europe : the future of the common market - Shanks, Michael; Lambert, John (London : Chatto & Windus, 1962)
Part 1 of the book traces the history of Britain's relations with Europe since the war. The second and longest part of the book deals with the common market and the other European institutions. Part 3 attempts to the future of the European community
Includes bibliography, index
osc 31/10/2018
Loans
Keywords: Economic cooperation